Study of some contention techniques for gathering tarantula venom - Diana Cimpian; Larisa Schuszler; T. Romeo Cristina (Medicamentul Veterinar)
The study of various types of venom has become a priority in the last years for medical sciences and biology Tarantula venoms represent a natural wealth of combinations of chemical compounds that attract more and more attention of pharmacologists. Over the last decade, these venoms have been studied to ultimately generate solutions: strong, selective bioactive products for medicine, but harvesting tarantula venom are a real challenge. In this respect, this initial present study aims to identify and analyze several methods of contention and anesthesia to allow operators an easier access to gathering the tarantula venom. Also due to scientific parsimony in relation to these venoms, data and specific uses in biology and medicine, we considered it necessary to present more in detail the main concerns of science on this topic at this time.